Pass/Fail, A-F, or 0-100? Optimal grading of eager students - Lilo Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This paper analyzes optimal grading in a world that focuses on top grades. Students choose an effort level, their performance is graded, and their grade correlates with their future income. Ex-ante, the policy maker chooses the optimal coarseness of the grading scale to maximize student welfare. When choosing their effort, students overweight outstanding - or salient - grades. I show that this behavior leads to excessive effort levels when grading is fully informative, and that coarse grading can be used to counterbalance incentives. Thus, salience can help explain why grading ranges from Pass/Fail scales (tenure decisions) via A-F-scales (school) to fully disclosing scores (e.g. SAT).
Keywords: D83; D81; I21; 330; Optimal Grading; Effort Incentives; Salience Theory; Education